Economical Synthesis of Nitrophenols under Controlled Physical Parameters: Economical Synthesis of Nitrophenols under Controlled Physical Parameters - Hussain, Shabbir; Ahmad, Muhammad Ameen; Ahmad, Muhammad; Nisar, Asma; Asghar, Amina; Suleman, Muhammad; Barkaat, Samra; Riaz, Muhammad; Nasir, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Current studies were performed to find an economical path for the synthesis of nitrophenols which are plant growth regulators (PGR) and are applied to crops for better agricultural production. The study discourages the involvement of costly surfactants such as CTAB, TBAB, H-β and γ-alumina catalysts in commercial production of nitrophenols. This synthesis requires the lower number of chemicals, less time and does not involve the advance instruments. Phenol and its derivatives were selectively nitrated into o/p nitrophenols economically by controlling only the physical parameters, i.e., dilution of nitric acid, reaction time and reaction temperature. The synthesised products were characterised by RP-HPLC and gas chromatography. The reaction between 98% phenol and 32.5% nitric acid at a temperature of 20°C (±2°C) required only 1 hour for optimum yield (91%) of nitrophenols with 77% ortho and 14% para selectivity and was found to have the most suitable route for economical production. The investigated synthetic path is relatively clean and environmentally friendly as it does not involve catalysts and solvents, like the conventional processes. This process may be adopted for commercialisation and industrial level production of nitrophenols for agricultural purposes.